KAJIAN ANALISIS WACANA KRITIS TERHADAP PEMBERITAAN VAKSIN COVID-19 PADA MEDIA ONLINE KOMPAS.COM - Fathur Rahmi Afdhila; Emeraldy Chatra; Asmawi Asmawi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The Covid-19 vaccination program is currently being discussed as a strategic effort in resolving the Covid-19 pandemic in Indonesia. Positive news related to the Covid-19 vaccination program currently dominates media coverage, one of which is the online Kompas.com. This study aims to reveal the textual strategy and packaging of the Covid-19 vaccine news text in representing the dominant discourse, using Van Dijk's critical discourse analysis model through analysis of the dimensions of the text structure. This study uses a qualitative method with a critical paradigm. The critical paradigm is used to see how the media here creates a certain way of thinking or discourse that is dominant and considered correct, so that it becomes an idea that is accepted as common sense by the community. The data used in this study were in the form of news on the Covid-19 vaccine on online, and literature studies. The results of the study show that the news of the Covid-19 vaccine on Kompas.com as a whole supports a positive view of the Covid-19 vaccination program through language strategies which include information control, diction selection, message packaging and various other efforts to support the construction of reality developed by the media.